A novel functional polymorphism of GSTM3 reduces clear cell renal cell carcinoma risk through enhancing its expression by interfering miR‐556 binding. Issue 6 (22nd March 2018) - Wang, Ying; Yang, Zi‐Ying; Chen, Yi‐Huan; Li, Feng; Shen, Han; Yu, You; Huang, Hao‐Yue; Shen, Zhen‐Ya
Abstract: Dysregulation of glutathione‐S‐transferase M3 ( GSTM3 ) has been related to clear cell renal cell carcinoma (ccRCC) in our former study. GSTM3 plays a pivotal role of detoxification and clearance of reactive oxygen species (ROS) in tumour tissues. This study aimed to examine: (1) the associations between GSTM3 single nucleotide polymorphisms (SNPs) and risk of ccRCC, and (2) the potential molecular mechanism accounting for its effects. 5 SNPs in 3′UTR of GSTM3 were initially genotyped in 329 cases and 420 healthy controls. A SNP‐rs1055259 was found to be significantly associated with the susceptibility of ccRCC (OR = 0.59, 95% CI = 0.41‐0.92; P  =   .019). The minor allele of rs1055259 (G allele) was associated with RCC risk. This SNP was predicted to affect microRNA (miR)‐556 binding to 3′UTR of GSTM3 mRNA. To determine the functional impact, plasmid constructs carrying different alleles of rs1055259 were created. Compared to rs1055259 A‐allele constructs, cells transfected with rs1055259 G‐allele construct had higher transcriptional activity and were less responsive to miR‐556 changes and gene expression. Elevated GSTM3 expression in G‐allele cells was associated with ROS activity and ccRCC development. Taken together, this study indicated that a functional polymorphism of GSTM3 ‐rs1055259 reduced susceptibility of RCC in the Chinese population. It influenced GSTM3 protein synthesis by interfering miR‐556 binding, subsequently suppressed ROS activity and ccRCC progression.